EDUKASI KESEHATAN SEKSUAL REMAJA UNTUK MENINGKATKAN PENGETAHUAN DAN SIKAP REMAJA TERHADAP PELECEHAN SEKSUAL DI SMPN 27 SELUMA - Sari, Lezi Yovita; Yulianti, Syami; Lestari Nurjanah, Nimas Ayu (LPPM STIKES BHAKTI HUSADA BENGKULU, 2024)
Background: Sexual violence is a sexual practice that is considered deviant because it is carried out in violent ways, contrary to religious teachings and values and violating applicable laws. According to Komnas Perempuan, one form of sexual violence is sexual harassment. The aim of the research is to determine whether there is a relationship between Adolescent Sexual Health Education to Increase Adolescents' Knowledge and Attitudes towards Sexual Harassment at SMPN 27 Seluma.Methods: This study used an analytic design with a cross sectional approach. The number of samples in this study were 35 people. Where the population of all female students I at SMPN 27 Seluma was used as a sample. Sampling in this study using the total population. This research was conducted at SMPN 27 Seluma in 2022. Data analysis used a bivariate test with chi-cquare.Results: The results of the study were the relationship between knowledge and sexual harassment, namely the knowledge of the majority of young women in the less category, namely 17 people (48.6%), with mild sexual harassment, namely 2 people (5.7%), moderate, namely 8 people (22.9%) ) and weight, namely 7 people (20.0%). The relationship between the attitudes of young women and sexual harassment, namely the attitude of the majority of young women was negative, namely 18 people (51.4%) with mild sexual harassment, namely 2 people (5.7%), moderate, namely 10 people (28.6%) and severe, namely 6 people (17.1%). The conclusion is that there is a relationship between the level of knowledge and attitudes of young women and sexual harassment of female students at SMPN 27 Seluma in 2022 with a significant value of 0.001 <0.05Conclusion: It is recommended for young women to increase their knowledge and attitudes about sexual harassment so that young women can prevent the negative impacts caused by sexual harassment.Keywords: Knowledge, Attitude, Young Women, Sexual Harassment